Phase structure of three and four flavor QCD - Fischer, Christian S.; Lücker, Jan; Welzbacher, Christian Andreas (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
We investigate the phase structure of QCD at finite temperature and light-quark chemical potential. We improve upon earlier results for Nf=2+1 dynamical quark flavors and investigate the effects of charm quarks in an extension to Nf=2+1+1. We determine the quark condensate and the Polyakov loop potential using solutions of a coupled set of (truncated) Dyson-Schwinger equations for the quark and gluon propagators of Landau gauge QCD. At zero chemical potential we find excellent agreement with results from lattice-QCD. With input fixed from physical observables we find only a very small influence of the charm quark on the resulting phase diagram at finite chemical potential. We discuss the location of the emerging critical end point and compare with expectations from lattice gauge theory.